An Inventory and Analysis of Conservation Status of Freshwater Fish Species in Palangka Raya City Traditional Markets - Septya, Lia; Wanto, Wahyu Anggar (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Freshwater fish is a source of animal protein that is often consumed. Palangka Raya, as one of the cities in Indonesia which has quite high diversity of freshwater fish, uses this to fullfill protein needs of its people. The aim of this research is to inventory the species of freshwater fish that are often traded in Palangka Raya traditional markets and their conservation status. The method used was a survey at four traditional markets in Palangkaraya City. The results obtained were 26 species of freshwater fish found in four markets. The 26 species consist of 11 families. The Cyprinidae family is mostly traded in the traditional markets of Palangka Raya City. As many as 91.6% of the fish species found were included in the Least Concern (LC) category according to the IUCN, while 8.3% were included in the Near Threatened (NT) category. The conclusion of this research is that the majority of freshwater fish traded in traditional markets in the city of Palangka Raya are still in the non-threatened category, but this needs to continue to be monitored to maintain ecosystem stability and support freshwater fish conservation efforts in Palangkaraya.